Appendiceal phlegmon in adults: Do we know how to manage it yet?. (November 2020) - Panahi, Pedram; Ibrahim, Rashid; Veeralakshmanan, Pushpa; Ackah, James; Coleman, Mark
Abstract: A Best Evidence Topic in general surgery was written according to a structured protocol. The question addressed was 'Appendiceal phlegmon in adults: Do we know how to manage it yet?'. Altogether 217 papers were found on Ovid Embase and Medline, 334 on PubMed and 13 on the Cochrane database using the reported search. From the screened articles, 5 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. We conclude that the best management method is conservative only treatment without interval appendicectomy. These patients must be followed up, including colonoscopy and/or CT imaging as indicated, to investigate for conditions such as inflammatory bowel disease or malignancy masquerading as appendicitis. Highlights: On-going controversy exists around the best management option for an appendiceal phlegmon. Various articles advocate each of the following: early appendicectomy, interval appendicectomy and conservative management. Therefore, we conducted a literature review in the format of a Best Evidence Topic to identify the best approach. We conclude that the best management method is conservative only treatment without interval appendicectomy. They must be followed up, including colonoscopy/imaging as indicated, to identify conditions masquerading as appendicitis. Our suggestion is in direct contrast to the widely practiced method of interval appendicectomy.